Unpacking students’ modelling behaviour in the Sun-Earth system: Use of digital media tool-based epistemological resources (International Conference on Computers in Education, 2020)
Understanding scientific models described using external representations is an important objective of science education. However, modelling and reasoning using models are not easy for students due to inaccessible phenomena or abstracted/ idealized nature of the models. Learners rely on various epistemological resources to make sense and meaning of the models in any given context. However, the underlying processes and the interplay of these resources in the process of constructing and reasoning with these models are not completely understood. We use the case of the Sun-Earth system to unravel these dynamics, by a detailed study of 4 undergraduate (UG) science students, using questionnaires and interviews around interactions with a digital media tool (designed by us). The results throw some light on the dynamics of students’ use of various epistemological resources (lived experiences, book-based, and tool-based experiences) in their process to construct models and reason with them. We also illustrate, in this process, a potential role of digital media interfaces in providing epistemic access to the inaccessible by being an epistemological resource of a new kind.